From Money to Merely a Precious Metal: A Historical Journey of Gold in Muslim World and Gold’s Price Correlation with Other Financial Indicators in the Contemporary Financial System - Kamola Bayram; Adam Abdullah (Türkiye İslam İktisadı Dergisi)
For many centuries Islamic coins, such as the dīnār (pl. danānīr), have attracted the attention of historians and chroniclers. The initial appearance of Islamic coinage came as a response to economic requirements prevailing in the Middle East following the Arab invasion. The motivation behind the inception of Islamic coinage was in absolute harmony with the monetary traditions of the Near Eastern economy. Even though, the external features of the coinage might have been influenced by some sociopolitical factors, their intrinsic value was determined by the contemporary economic conditions. During periods 1870-1930 the world monetary system was mainly built on gold. However, with the establishment of Bretton Woods System in 1944, the world was set on the new monetary system involving a fixed exchange rate system. With the collapse of the Bretton Woods system in 1971 the price of gold increased to USD 38 per ounce. In April 1974, following the high volatility in monetary markets and oil crisis the price of gold increased 453% and reached USD 172 per ounce. As the U.S. economy increased in power, the I.M.F. diminished the monetary role of gold so that subsequently, gold was viewed as merely a precious metal commodity that was subject to a market value and changes in the price of gold. This article examines the monetary history of gold during Rashidun, Umayyad, Abbasid, Fatimid and Ottoman Caliphates. In particular, this study focuses on golds’ performance during global financial crisis of 2007-2009 (GFC) and correlation analysis is conducted to measure the strength and direction of a linear relationship between gold and other selected asset classes as well as financial indicators such as real interest rates, inflation rates, silver price, Dow Jones Industrial Average, Trade Weighted U.S. Dollar Index, money supply and crude oil prices.